Co-creating Public Library Futures: An Emergent Manifesto and Participatory Research Agenda. Issue 1 (2nd January 2022) - Swist, Teresa; Hendery, Rachel; Magee, Liam; Ensor, Jason; Sherman, Jen; Budge, Kylie; Humphry, Justine
ABSTRACT : Public libraries occupy a highly visible and promissory role for how individuals and communities learn, interact and share with one another. Yet libraries are increasingly underfunded, decried as outdated or irrelevant, or swept up in neoliberal agendas and financialised logics. Combined, these threaten the public library as an indispensable site for community collection and re-collection. Inspired by previous library-focused position statements, a workshop, and subsequent experimental writing exercise, we offer our own manifesto for co-creating public library futures . In this, we seek to unpack the tensions that encircle public libraries and seek to chip away at their physical, digital and social infrastructure. Due to the way in which public libraries can co-create multiple possibilities, we argue that this manifesto be used to inform future participatory research agendas. The key message is hopeful, yet pragmatic: co-creating public library futures can support social justice efforts yet requires ongoing vigilance and new forms of institutional and societal investment.